2021
DOI: 10.1108/jec-08-2021-0112
|View full text |Cite
|
Sign up to set email alerts
|

Capture coproduction behavior in networking alumni communities: Progress from platform belongingness, knowledge sharing, and citizenship behavior

Abstract: Purpose The purpose of this study is to investigate coproduction behavior in networking alumni communities via the progress from platform belongingness, knowledge sharing and citizenship behavior. Alumni networking communities have emerged as valuable assets for conserving institutional resources, supporting members and contributing new resources for alumni-institutional professional development. However, the previous literature has not yet captured the explicit processes by which these contributions are made.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…(3) Mediating variable: The need for achievement (NA) refers to the need of users to achieve goals and pursue excellence based on their own interests and passions [ 43 ], so it was represented by the number of cheers users get in the OnePlus Community [ 56 ]. The need for power (NP) refers to the user’s need to influence or control others by acquiring social status [ 56 ], so it was indicated by the different user group levels that users belong to in the community.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Mediating variable: The need for achievement (NA) refers to the need of users to achieve goals and pursue excellence based on their own interests and passions [ 43 ], so it was represented by the number of cheers users get in the OnePlus Community [ 56 ]. The need for power (NP) refers to the user’s need to influence or control others by acquiring social status [ 56 ], so it was indicated by the different user group levels that users belong to in the community.…”
Section: Methodsmentioning
confidence: 99%
“…Liu and Li indicated that users’ interaction behaviors, including help-seeking, interaction and social behaviors, have a significant impact on their value co-creation behaviors [ 42 ]. Bui & Jeng pointed that user’s sense of belonging can affect user’s citizenship behavior [ 43 ]. On the other hand, from the perspective of communities, researchers have examined their governance mechanisms, incentives, and climates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Knowledge supply Knowledge Sharing [9,16,43] Knowledge Contribution [4,19,44] Knowledge Supply [8] Knowledge Gathering [22] Knowledge Creation…”
Section: Classification Of Users Based On Knowledge Behavior Type Of ...mentioning
confidence: 99%
“…Knowledge demand Knowledge Search [20] Knowledge Assessment [18] Knowledge Filtering [45] Knowledge Adoption [9] Knowledge Utilization [10] Knowledge Reuse [46] Bidirectional behavior Knowledge Exchange [15,40,47] Knowledge Transformation [4,11] Knowledge Transfer [22,38] From the perspective of knowledge supply, previous studies have mainly investigated the antecedents and consequences that influence user knowledge contribution or knowledge sharing from the perspectives of internal and external motivation, social capital, social cognition, and organizational climate. For example, Liu, Yang [48] applied collective action theory to verify the effects of individual motivation and social capital on knowledge contribution and found that structural capital had the most significant effect on knowledge sharing in OICs.…”
Section: Classification Of Users Based On Knowledge Behavior Type Of ...mentioning
confidence: 99%
See 1 more Smart Citation